Sex, Pramipexole and Tiagabine Affect Behavioral and Hormonal Response to Traumatic Stress in a Mouse Model of PTSD - Malikowska-Racia, Natalia; Salat, Kinga; Gdula-Argasinska, Joanna; Popik, Piotr (Frontiers in Pharmacology, 2021)
Posttraumatic stress disorder (PTSD) has been associated with abnormal regulation of the hypothalamic-pituitary-adrenal gland axis (HPA). Women demonstrate a more robust HPA response and are twice as likely to develop PTSD than men. The role of sex hormones in PTSD remains unclear. We investigated whether post-trauma chronic treatment with the GABA-ergic agent tiagabine and dopamine-mimetic pramipexole affected the behavioral outcome and plasma levels of corticosterone, testosterone, or 17β-estradiol in female and male mice. These medications were investigated due to their potential capacity to restore GABA-ergic and dopaminergic deficits in PTSD. Animals were exposed to a single prolonged stress procedure (mSPS). Following 13-days treatment with tiagabine (10 mg/kg) or pramipexole (1 mg/kg) once daily, the PTSD-like phenotype was examined in the fear conditioning paradigm. Plasma hormones were measured almost immediately following the conditioned fear assessment. We report that the exposure to mSPS equally enhanced conditioned fear in both sexes. However, while males demonstrated decreased plasma corticosterone, its increase was observed in females. Trauma elevated plasma testosterone in both sexes, but it had no significant effects on 17β-estradiol. Behavioral manifestation of trauma was reduced by pramipexole in both sexes and by tiagabine in females only. While neither compound affected corticosterone in stressed animals, testosterone levels were further enhanced by tiagabine in females. This study shows sex-dependent efficacy of tiagabine but not pramipexole in a mouse model of PTSD-like symptoms and a failure of steroid hormones' levels to predict PTSD treatment efficacy.